MRNA methylation in cell senescence. (29th May 2019) - Casella, Gabriel; Tsitsipatis, Dimitrios; Abdelmohsen, Kotb; Gorospe, Myriam
Abstract: Cellular senescence, a developmental program central to normal aging and aging pathologies, is robustly regulated at the post‐transcriptional level. This regulation involves the interaction of RNA‐binding proteins and noncoding RNAs with senescence‐associated messenger RNAs (mRNAs). There is increasing evidence that these associations are modulated by chemical modifications of specific mRNA nucleotides which can enhance or reduce the binding of regulatory factors. Recent technological advances in mass spectrometry, next‐generation sequencing, and genome mapping have improved markedly the detection of mRNA modifications. Given the rising interest in the epitranscriptomic control of gene expression in aging, we discuss our incipient understanding of the chemical mRNA modifications, specifically m 6 A and m 5 C, that influence cellular senescence. This article is categorized under: RNA Export and Localization > RNA Localization RNA Processing > RNA Editing and Modification Abstract : Main regulatory modifications reported in mRNAs encoding senescence‐associated proteins, m6A and m5C. Each modification can promote (green) or repress (purple) protein expression from the respective mRNAs.